2013
DOI: 10.5489/cuaj.1338
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to estimate renal volume from computed tomography

Abstract: Introduction: Renal parenchymal volume can be used clinically to estimate differential renal function. Unfortunately, conventional methods to determine renal volume from computed tomography (CT) are time-consuming or difficult due to software limitations. We evaluated the accuracy of simple renal measurements to estimate renal volume as compared with estimates made using specialized CT volumetric software. Methods: We reviewed 28 patients with contrast-enhanced abdominal CT. Using a standardized technique, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…a For example, the adjusted 5-year functional gain regarding age at donation in model 1 is 20.3, meaning that, for an additional 1 year of age, the 5-year functional gain will be reduced by 0. The adjusted volume of the kidney estimated using the ellipsoid equation (19) was highly correlated with the adjusted kidney volume measured using renal CT scan (R=0.82; P,0.001). We tested our model using the rk-GFR/vol computed with the volume estimated with the ellipsoid equation and found that rk-GFR/vol is still statistically significant at the 5% level and that the predictive power of the model is as high as the model that included kidney volume measured using renal CT scan (R 2 =0.41 with estimated volume).…”
Section: Determinants Of the Gain Of Function Of The Remaining Kidneymentioning
confidence: 93%
See 1 more Smart Citation
“…a For example, the adjusted 5-year functional gain regarding age at donation in model 1 is 20.3, meaning that, for an additional 1 year of age, the 5-year functional gain will be reduced by 0. The adjusted volume of the kidney estimated using the ellipsoid equation (19) was highly correlated with the adjusted kidney volume measured using renal CT scan (R=0.82; P,0.001). We tested our model using the rk-GFR/vol computed with the volume estimated with the ellipsoid equation and found that rk-GFR/vol is still statistically significant at the 5% level and that the predictive power of the model is as high as the model that included kidney volume measured using renal CT scan (R 2 =0.41 with estimated volume).…”
Section: Determinants Of the Gain Of Function Of The Remaining Kidneymentioning
confidence: 93%
“…The workup before donation included urinary albumin-to-creatinine ratio (ACR) on the second morning urinary spot measurement, 24-hour ambulatory BP measurement (ABPM) to depict hypertension according to the current guidelines (18), 51 Cr-EDTA GFR measurement, and SRF using renal scintigraphy (12). For 52 of the donors, the initial volume of the remaining kidney was measured using CT scan and also estimated with the ellipsoid equation (19) using only the measurements of the length, the lateral diameter, and the anterior-posterior diameter of the kidney on CT scan. Renal scintigraphy and methods to measure GFR and kidney volume are described in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…1 The authors found that the ellipsoid method underestimated 3D volume (170 cm 3 vs. 186 cm 3 , respectively), but that almost all were accurate 30%; they also concluded that measuring renal volume is easy and reliable. They also suggested that 3D volume software is not needed for the estimation of differential renal function.…”
mentioning
confidence: 99%
“…http://dx.doi.org/10.5489/cuaj.1336 W e congratulate Breau and colleagues for demonstrating that there was good correlation between renal volume as measured by two techniques: the ellipsoid method and 3D volume measurement using specialized volumetric software with contrast-enhanced CT scans. 1 The authors found that the ellipsoid method underestimated 3D volume (170 cm 3 vs. 186 cm 3 , respectively), but that almost all were accurate 30%; they also concluded that measuring renal volume is easy and reliable. They also suggested that 3D volume software is not needed for the estimation of differential renal function.…”
mentioning
confidence: 99%
See 1 more Smart Citation